The urban landscape heritage as a social participative and artistic construct. The case study of Mouraria in Lisbon - Moya, Ana (CEM – Cultura, Espaço & Memória, 2021)
Migrations, mass tourism, and international real estate investments are causing irreversible effects on the genuine identity evolution of Mouraria’s urban landscape heritage. This research analyses the emotional and multisensorial responses to the urban space of Mouraria’s residents using the methodology of three pedagogical-artistic laboratories. We enquire how this multicultural community is involved in the creation of an active and predicative experience of space through artistic activities. This community-based research reaffirms the understanding of the urban heritage in its intangible dimension as a social participative construct, in a constant process of identity reformulation, reinvention, and artistic creation.